Design & Simulation of Microstrip Trapezoidal Patch Antenna with H and V Shaped slot - Gyanender Kumar, Pooja Garg, Abhishek Gupta, (International Journal of Scientific Research and Management (IJSRM), 2015)
This paper consists of two small Microstrip patch antenna. with H shaped and V shape slot. A trapezoidal patch is designed ona RT duroid substrate with relative permittivity of 2.2 and height of 6mm. A series of parametric study were carried out to showthe dependence of the characteristics of the antenna on its various geometrical parameters Microstrip antenna is widely usedin practical applications like wi-fi, wlan etc An Soft HFSS Vs 12 software which is based on finite element method , showedsatisfactory performance with VSWR